ANALISIS KAMPANYE TENTANG DOXING DALAM UPAYA MENJAGA DATA PRIBADI DI MEDIA SOSIAL - Mellania, Putri (Sintesa, 2025)
This study aims to analyze the #PrivacyMatters campaign conducted by Instagram in an effort to protect users' personal data and prevent doxing practices on social media. In using social media, society is required to constantly update their daily lives by sharing them using features available on these platforms. The term "doxing" became popular in the 1990s, when hackers would gather personal information of individuals targeted in hacking attacks. Doxing, referring to the act of spreading someone’s personal information without consent, is a serious threat in the context of digital privacy. Given the importance of protecting personal data, this campaign focuses on educating users to pay more attention to their privacy settings and data safety. This research uses a qualitative approach with a content analysis method to explore the effectiveness and impact of the campaign. Data is collected through the analysis of campaign content, which includes examining the types and formats of content, hashtag usage, message strategies, communication styles, and surveys measuring user responses to the messages delivered. The findings of the study indicate that the #PrivacyMatters campaign successfully increased user awareness of the importance of protecting their personal data and reduced risky behavior related to sharing personal information. However, challenges in reaching all segments of users who are less concerned with privacy remain a barrier. The study concludes that campaigns like this need to be conducted continuously and updated to address changes in user behavior and platform policies. As a recommendation, social media platforms like Instagram need to continually strengthen privacy education strategies and collaborate with various parties to create a safer digital ecosystem. Overall, while Instagram provides limited control over personal data, users need to be cautious when sharing sensitive information and understand the platform's privacy policies. Keywords: Campaign, Doxing, personal data, Instagram Social Media